Detection of polymorphism in AgB1 gene from sheep, cattle and human isolates of echinococcus granulosus by SSCP - Simsek, Sami; Ozcetin, Cagri; Balkaya, Ibrahim (Elsevier Science Bv, 2012)
Antigen B (AgB) is a major protein produced by the metacestode cyst of Echinococcus granulosus, the causative agent of cystic hydatid disease. E. granulosus AgB is a gene family of at least five gene loci (B1-B5), each one consisting of several minor variants. We used PCR-SSCP followed by DNA sequencing to evaluate sequence variation and polymorphism of AgB1 in 99 isolates which the 43 were from cattle, 25 of sheep and 31 of human. All samples were analyzed with 12S rRNA-PCR for the strain detection and all of were identified as G1-G3 cluster (E. granulosus sensu stricto). The 16 human, 35 cattle and 25 sheep isolates were yielded the 102 bp band by PCR and these samples were tested by SSCP. As results of the SSCP, different band profiles were detected one each of cattle and human isolates while the other 74 isolates showed same band patterns. The DNA sequence analysis was performed for these two isolates and the other selected 4 isolates and polymorphism was confirmed. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Echinococcus granulosus; AgB1 gene; SSCP; Polymorphism; PCR